PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI GRAND SOVIA HOTEL BANDUNG - Olis Holisoh; Aep Saefuddin (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2025)
Digital transformation has reshaped the way customers evaluate hotel services through online reviews and ratings, making service quality a critical factor in shaping customer satisfaction. Grand Sovia Hotel Bandung, a three-star hotel with a strategic location, faces challenges in meeting increasingly high guest expectations, as reflected in negative customer reviews. This study aims to analyse the effect of service quality on customer satisfaction at Grand Sovia Hotel Bandung and to determine the magnitude of this effect. A quantitative research approach was employed using accidental sampling with 100 respondents. Data were analysed using simple linear regression. The results indicate that service quality has a positive and significant effect on customer satisfaction, with a regression coefficient of 0.918 and a calculated t-value of 54.219 exceeding the critical t-value of 1.661 at a significance level of 0.000. The coefficient of determination (R²) of 0.968 indicates that 96.8% of the variation in customer satisfaction is explained by service quality, while the remaining proportion is influenced by factors beyond the scope of this study. These findings support SERVQUAL theory and confirm that tangibles, reliability, responsiveness, assurance, and empathy are the primary determinants of customer satisfaction.